Optimizing Dynamic Airlift Operations: Winning Strategies in the AFRL Airlift Challenge - John Kolen (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
The Air Force Research Laboratory (AFRL) has sponsored the Airlift Challenge over the past two years, aimed at addressing the dynamic airlift problem. The dynamic nature of the challenge included the random disappearance of graph edges to simulate adverse weather conditions and the spontaneous appearance of cargo requiring delivery. This poster presents the systems that won both the 2023 and 2024 challenges. The initial approach focused on intelligent solutions for subtasks, or 'build-smart'. It soon became clear that the optimization of the scoring rate, points per second, was more important than single instance metric performance. In the subsequent competition, a 'build-fast' strategy was adopted due to this observation. This paper discusses the impact of iteration on algorithm selection for optimization problems and suggests considerations for structuring scoring processes in future competitions.